2023
DOI: 10.1039/d2sc06935k
|View full text |Cite
|
Sign up to set email alerts
|

Chemical signal regulated injectable coacervate hydrogels

Abstract: Incorporation of reversible Michael addition controlled coacervate crosslinks in a polymer hydrogel led to injectable gels that are responsive to nucleophilic chemical signals, enabling accelerated degradation in culture media after injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…61,62 Furthermore, cytotoxicity of even small-molecule Michael acceptors strongly depends on their structure, making biomedical applications possible depending on the choice of molecules. 63 Conjugate additions always involve the attack of a carbon-or heteroatom-centred nucleophile, i.e. Michael donor, on an electronpoor, unsaturated electrophile, called the Michael acceptor (Scheme 2A and B).…”
Section: Versatility and Drawbacks Of Conjugate Additionsmentioning
confidence: 99%
See 1 more Smart Citation
“…61,62 Furthermore, cytotoxicity of even small-molecule Michael acceptors strongly depends on their structure, making biomedical applications possible depending on the choice of molecules. 63 Conjugate additions always involve the attack of a carbon-or heteroatom-centred nucleophile, i.e. Michael donor, on an electronpoor, unsaturated electrophile, called the Michael acceptor (Scheme 2A and B).…”
Section: Versatility and Drawbacks Of Conjugate Additionsmentioning
confidence: 99%
“…61,62 Furthermore, cytotoxicity of even small-molecule Michael acceptors strongly depends on their structure, making biomedical applications possible depending on the choice of molecules. 63…”
Section: Introductionmentioning
confidence: 99%
“…We were inspired to investigate nucleophile responsive polycations after our recent work demonstrating controlled (de)cationization of polyvinylpyridine (PVP) copolymers by successive additions of an allyl acetate (ionization), and S/N-nucleophiles (deionization). 24,25 With an appropriate polyanion, the PVP copolymers (dis)assembled into coacervate core micelles, effectively achieving signal controlled polyanion encapsulation and release. 26 Importantly, we found that the decationiziation reaction is significantly faster for thiols compared to primary amines (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the physical and chemical properties of hydrogels, they are widely used in the research of tissue engineering regeneration, especially for teeth with complex anatomical structures. Biocompatible hydrogels include injectable hydrogels [ 9 ], tissue-related hydrogels [ 10 ], nanocomposite hydrogels [ 11 ] and intelligent hydrogels [ 12 ]. Functional hydrogels are sensitive to physiological and pathological signals and have a wide range of biomedical applications [ 13 ].…”
Section: Introductionmentioning
confidence: 99%